Proteomic analysis of murine norovirus-infected Raw 264.7 cells reveals the induction of Ras GTPases - Sung Ho Yun; Md Arif-Ur Rahman; Soo-Bin Nam; Soo Hyeon Kim; Gyuri Kim; Kun Cho; Jong-Soon Choi (Journal of Analytical Science and Technology)
Abstract The human norovirus (abbreviated as HuNV) is the most common agent responsible for acute viral gastroenteritis. Despite being recognized as a water-borne pathogenic virus for a long time, the cellular tropism of norovirus has not yet been clearly explained. The main reason is the lack of appropriate cell culture and animal model systems for HuNV infection. Murine norovirus (abbreviated as MNV) is often used as a proxy for human norovirus when trying to understand the expression profiles left behind by norovirus infection in a host. In the current study, the host response to MNV was examined using the macrophage Raw 264.7 in terms of the altered host proteomes. After MNV infection, host Raw 264.7 cell lysates were collected for proteome profiling at the time points of 0.5 hpi (early phase, control), 16 hpi (mid-phase), and 24 hpi (late phase). LC–MS analysis was employed for label-free shotgun proteomics on the host cell proteomes. The progression of MNV infection status was monitored using an immunofluorescence-conjugated noroviral capsid protein VP1 and a confocal microscope. The up-regulation of Ras GTPases such Rab5A and Rab6A was found to be implicated in norovirus gastroenteritis, as revealed by proteomic profiling. Consequently, the recognition of Ras-related proteins can lead to a better understanding of how noroviral infection affects the immune system of the host cell.